An account of alternative and complementary medicine and its scope in a clinical scale - Maduskar, Saumil (International Journal Of Community Medicine And Public Health, 2021)
Background: Alternative medicine is the practice of using alternative therapies as treatment modalities and complementary medicine is their inculcation with conventional medical practices. The purpose of this article was to judge people’s perception of these practices and assess societal attitude towards alternative and complementary medical practices. Methods: A survey was conducted among non-medical professionals to assess their attitude towards alternative medicine. They were asked questions with multiple choices to choose from in order to grade their attitude towards and comprehension of alternative and complementary medicine. The questions were designed in a way so as to demand responses ranging from their last visit to an alternative medical therapist to their reason for their visit and their experience. Results: It was observed that most people surveyed were aware of the difference between conventional and complementary medicine but usually visited an alternative therapist without consulting their physician. It was documented that most people were misguided about the actual benefits of complementary medical practices and a majority of the surveyed population chose either alternative medicine or conventional medicine but very few were willing to integrate the two. Conclusions: Alternative medicine is extremely beneficial when used in tandem with conventional medicine and provides numerous benefits. Its use and propagation however must be strictly monitored in order to prevent quackery and the spread of misconceptions regarding its effects.